The Relationship between Personality Traits and Job Satisfaction among Healthcare Professionals: a Comparative Analysis of Personality and Occupational Satisfaction - Kostić, Marina (Medical Word, 2026)
Job satisfaction is recognized as one of the key indicators of mental health and professional efficacy in the healthcare sector. Physicians, specialists, nurses, and clinical technicians represent some of the most frequently examined populations in psychological research on personality, occupational stress, job satisfaction, and burnout, due to their frequent exposure to emotionally demanding and high-responsibility work environments. Given the intense demands, elevated accountability, and the inherently stressful nature of their roles, healthcare professionals face complex emotional, cognitive, and interpersonal challenges, making the understanding of factors contributing to job satisfaction particularly significant. The aim of this review paper is to examine the association between personality traits and professional satisfaction among healthcare professionals through an analysis of contemporary theoretical models, relevant scientific publications, and empirical findings. Special emphasis is placed on individual differences in personality characteristics and their influence on perceptions of the work environment, quality of interpersonal relationships, and the subjective experience of professional purpose. Findings from recent studies suggest that traits such as emotional stability, conscientiousness, and openness to experience are positively associated with higher levels of job satisfaction, whereas traits like neuroticism are predictive of professional dissatisfaction and occupational burnout. This paper synthesizes data from international studies conducted in diverse clinical and hospital settings, with the goal of identifying and comparing dominant patterns in the relationship between personality traits and subjective professional well-being. In conclusion, the paper discusses implications for personnel selection, the development of psychological support systems, and the design of organizational interventions aimed at promoting job satisfaction and safeguarding the mental health of healthcare professionals.